Joe Celko's SQL puzzles & answers - Celko, Joe. (San Francisco, Calif. : Morgan Kaufmann Publishers, 2007)
In this complete revision and expansion of his first SQL Puzzles book, Joe Celko challenges you with his trickiest puzzlesand then helps solve them with a variety of solutions and explanations. Joe demonstrates the thought processes that are involved in attacking a problem from an SQL perspective to help advanced database programmers solve the puzzles you frequently face. These techniques not only help with the puzzle at hand, but help develop the mindset needed to solve the many difficult SQL puzzles you face every day. Of course, part of the fun is to see whether or not you can write better solutions than Joes. * A great collection of tricky SQL puzzles with a variety of solutions and explanations. * Uses the proven format of puzzles and solutions to provide a user-friendly, practical look into SQL programming problems - many of which will help users solve their own problems. * New edition features: Many new puzzles added! Dozens of new solutions to puzzles, and using features in SQL-99 Code is edited to conform to SQL STYLE rules New chapter on temporal query puzzles New chapter on common misconceptions about SQL and RDBMS that leads to problems.
PUZZLE 01: FISCAL YEAR TABLES -- PUZZLE 02: ABSENTEES -- PUZZLE 03: THE ANESTHESIA PUZZLE -- PUZZLE 04: SECURITY BADGES -- PUZZLE 05: ALPHA DATA -- PUZZLE 06: HOTEL RESERVATIONS -- PUZZLE 07: KEEPING A PORTFOLIO -- PUZZLE 08: SCHEDULING PRINTERS -- PUZZLE 09: AVAILABLE SEATS PUZZLE -- PUZZLE 10: WAGES OF SIN: -- PUZZLE 11: WORK ORDER -- PUZZLE 12: CLAIMS STATUS -- PUZZLE 13: TEACHERS -- PUZZLE 14: TELEPHONE -- PUZZLE 15: FIND THE LAST TWO SALARIES -- PUZZLE 16: MECHANICS -- PUZZLE 17: EMPLOYMENT AGENCY -- PUZZLE 18: JUNK MAIL -- PUZZLE 19: TOP SALESMEN -- PUZZLE 20: TEST RESULTS -- PUZZLE 21: AIRPLANES AND PILOTS -- PUZZLE 22: LANDLORD -- PUZZLE 23: MAGAZINE -- PUZZLE 24 ONE IN TEN -- PUZZLE 25: MILESTONE -- PUZZLE 26: DATAFLOW DIAGRAMS -- PUZZLE 27: FINDING EQUAL SETS -- PUZZLE 28: CALCULATE THE SINE FUNCTION -- PUZZLE 29: FIND THE MODE COMPUTATION -- PUZZLE 30: AVERAGE SALES WAIT -- PUZZLE 31: BUYING ALL THE PRODUCTS -- PUZZLE 32: COMPUTING TAXES -- PUZZLE 33: COMPUTING DEPRECIATION -- PUZZLE 34: CONSULTANT BILLING -- PUZZLE 35: REQUISITIONS -- PUZZLE 36: DOUBLE DUTY -- PUZZLE 37: MOVING AVERAGE -- PUZZLE 38: JOURNAL UPDATING -- PUZZLE 39: INSURANCE LOSSES -- PUZZLE 40: PERMUTATIONS: -- PUZZLE 41: BUDGETING -- PUZZLE 42: COUNTING FISH -- PUZZLE 43: GRADUATION -- PUZZLE 44: PAIRS OF STYLES -- PUZZLE 45: PEPPERONI PIZZA -- PUZZLE 46: SALES PROMOTIONS -- PUZZLE 47: BLOCKS OF SEATS -- PUZZLE 48: UN-GROUPING -- PUZZLE 49: WIDGET COUNT -- PUZZLE 50: TWO OF THREE -- PUZZLE 51: BUDGET VERSUS ACTUAL -- PUZZLE 52: PERSONNEL PROBLEM -- PUZZLE 53: COLLAPSING A TABLE BY COLUMNS -- PUZZLE 54: POTENTIAL DUPLICATES -- PUZZLE 55: PLAYING THE PONIES -- PUZZLE 56: HOTEL ROOM NUMBERS -- PUZZLE 57: GAPS -- 1 -- PUZZLE 58: GAPS -- 2 -- PUZZLE 59: MERGING TIME PERIODS -- PUZZLE 60: BARCODES -- PUZZLE 61: SORTING A STRING -- PUZZLE 62: REPORT FORMATTING -- PUZZLE 63: CONTIGUOUS GROUPINGS -- PUZZLE 64: BOXES -- PUZZLE 65: AGE RANGES FOR PRODUCTS -- PUZZLE 66: FOUR CONSECUTIVE ABSENCES -- PUZZLE 67: STABLE MARRIAGES PROBLEM -- PUZZLE 68: CATCHING THE NEXT BUS -- PUZZLE 69: LIFO-FIFO INVENTORY -- PUZZLE 70: STOCK TRENDS -- PUZZLE 71: CALCULATIONS -- PUZZLE 72: SCHEDULING SERVICE CALLS -- PUZZLE 73: A LITTLE DATA SCRUBBING -- PUZZLE 74: DERIVED TABLES OR NOT? -- PUZZLE 75: FINDING A PUB.
Includes index.
Keywords: SQL (Computer program language).; Electronic books